Incorporating Utmost Good Faith into Vietnamese Insurance Law: Challenges for Effective Adoption - Nam, Bach Thi Nha (VNU Journal of Science: Legal Studies; Vol 42 No 1, 2026)
This article examines Vietnam’s recent reform of insurance law in June 2022, which incorporates the principle of utmost good faith, presenting a critical opportunity to distinguish it from the general principle of good faith in the Vietnamese Civil Code 2015. By analysing the application of utmost good faith in navigating the pre-contractual duties of disclosure and information provision for both insurers and policyholders, the article highlights potential challenges for effective adoption and offers solutions to harmonize its application and interpretation with the general good faith in the Civil Code. Effective adoption and implementation of the utmost good faith principle can foster a more transparent, consumer-friendly insurance market while ensuring the harmony of Vietnam’s legal system.